Pelatihan dan Pengembangan Mindset Kewirausahaan Para Siswa SMA Stella Duce Bambanglipuro Bantul 2025 - Dismas Persada Dewangga Pramudita; Agatha Mayasari; Maria Setyaningsih Nernere; Patricia Paramitha Suci; Raden Agoeng Bhimasta; Raymundo Patria Hayu Sasmita (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
Bernardus Foundation, an educational institution under the Archdiocese of Semarang, is committed to developing students’ entrepreneurial skills at Stella Duce Bambanglipuro Bantul High School in Ganjuran, Yogyakarta. Given the challenging employment situation, fostering an entrepreneurial mindset is essential to prepare students for the workforce and enable them to create business opportunities. Entrepreneurial character development also helps shape independent, creative, and adaptive individuals. This community service activity aimed to enhance students’ understanding of entrepreneurship through interactive discussions, simulations, and business idea presentation training. The program was implemented for students in grades X, XI, and XII, focusing on identifying business opportunities and developing marketing strategies based on local economic conditions. Mentoring sessions were conducted to ensure participants could understand and apply entrepreneurial concepts in real-life contexts. The results demonstrated high student enthusiasm and improved understanding of entrepreneurship as a promising career path. Through strengthened entrepreneurial awareness and motivation, students are expected to develop greater self-reliance and readiness for future challenges. Furthermore, this initiative is expected to contribute to economic development by encouraging entrepreneurship based on local potential.